Intercultural experiences and women's professional life stories for decolonial pedagogy - Isabella Pescarmona; Giulia Gozzelino (University of Bologna, 2023)
Promoting decolonial educational practices assumes the determination to step outside of unique, stereotyped and majority narratives and constantly deconstruct patterns, cultural hierarchies, and relations of domination in which we are involved. In this perspective, the contribution discusses some issues emerged from the narratives collected within the research path Women's voices, plural perspectives. Professional life stories in educational and intercultural contexts, recognising the contribution of women with a migration background as active constructors of generative actions and relationships in Italian socio-educational contexts. Through a series of meetings, dialogues and in-depth interviews, the project collected narratives and innovative and intercultural postures of twenty women activists and professionals. Listening to their stories challenges our educational contexts towards greater equity, denounces the persistence of intersectional discrimination and questions the ways of doing pedagogical research to develop a plural, shared and decolonial approach.